Research on the Coupling Mechanism of the Trade Union and Human Resource Management in China - Xuexiu, Fan; Jiandong, Sun (Frontiers in Psychology, 2022)
In recent years, with the reform of trade unions in China, there is an interaction between trade union and human resource management in the workplace. However, there is not a proper concept to describe such phenomenon. Therefore, based on reviewing the current literature involving trade union and human resource management in China, this study aims to describe such interactive relation between union's practices and enterprises' human resource management through arguing the definition, characteristics, and formation mechanism. This study defined the relation between trade union and human resource management as a coupling relationship which means that trade union and human resource management continually promote and restrain each other as two relatively independent systems in the enterprise. This relationship possesses three dual characteristics, namely reciprocity versus restraint, integrity versus independence, and stability versus dynamics. And there are three sequential stage for trade union and human resource management to form such relation, interaction, consensus, and adjustment. This study gives a further insight to the relation between trade union and human resource management in the workplace and give a proximately complete description to such relation, offering a direction for trade unions and enterprises to construct a high-quality cooperation with each other which is beneficial for enterprises' development and employee well-being.